2017
DOI: 10.14719/pst.2017.4.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicinal plant knowledge of some spermatophytes of Samar Bagh Valley, Lower Dir District, Pakistan

Abstract: The study on traditional knowledge of medicinal plants which are used by local people of Samar Bagh valley in district Lower Dir, Pakistan resulted in the report of 41 species of seed plants which belong to 37 genera and 30 families. Amongst them are 55% herbs, 25% shrubs, 17 % trees and 3% rhizome bearing species. The local peoples who use these plants for the treatment of various diseases were farmers, those who are raring of live stock and hakims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The occurrence of respiratory diseases remains high in both developed and developing countries. Most of these diseases for example, asthma, cough, pneumonia, whooping cough and chronic obstructive pulmonary disease (COPD) are preventable (Irfan et al 2017;Yeh & Horwitz, 2017). Respiratory disorders often occur as a result of polluted air, microbial infection and way of life while the jeopardy factors include air pollution, tobacco smoke and dusts as well as common lower respiratory infections during babyhood.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of respiratory diseases remains high in both developed and developing countries. Most of these diseases for example, asthma, cough, pneumonia, whooping cough and chronic obstructive pulmonary disease (COPD) are preventable (Irfan et al 2017;Yeh & Horwitz, 2017). Respiratory disorders often occur as a result of polluted air, microbial infection and way of life while the jeopardy factors include air pollution, tobacco smoke and dusts as well as common lower respiratory infections during babyhood.…”
Section: Introductionmentioning
confidence: 99%
“…About 80% people of all over the world still depend on the traditional system of health care [2]. New taxa of immense medicinal importance have been reported from various places in Pakistan [3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants have been widely used since ancient times due to their potential ability to alleviate or cure diseases [ 1 , 2 ]. Medicinal plants have been a vital source of both curative and preventive medical therapy preparations for human beings, and have been used for the extraction of important bioactive compounds [ 2 , 3 , 4 ]. The World Health Organization (WHO) has suggested that 80% of people prefer to use plant extracts to cure various diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%